If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -2 + 2x = 20 Reorder the terms: -2 + 5x + 2x = 20 Combine like terms: 5x + 2x = 7x -2 + 7x = 20 Solving -2 + 7x = 20 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + 7x = 20 + 2 Combine like terms: -2 + 2 = 0 0 + 7x = 20 + 2 7x = 20 + 2 Combine like terms: 20 + 2 = 22 7x = 22 Divide each side by '7'. x = 3.142857143 Simplifying x = 3.142857143
| (2x+1)x(3x-5)=0 | | 9(2-b)=b | | 3(5x+1)=15x+3 | | y=1.09x | | x+2=4x-3 | | 8x^2-29x-12= | | -5(-7x+5)= | | (3c^2-2d^2)(9c^2-6c^2d^2+4d^2)=0 | | (5x+4)(2x+2)= | | 18y^2+9y-2=0 | | 15x^2-8x+3=0 | | 2*3(-6*5)=x | | 4y=-5y+1 | | ln(x-3)=ln(7x-23)-ln(x+1) | | 9(n-3)=-18 | | 2v+8=4 | | -24=4x-4 | | n+36=28 | | 3-5=d | | x+1+1+6x=3(x-4)-(x-4) | | 4t-18=-53-9t | | 5c+20=30 | | .50x+.15(30)=28.5 | | 8p-18=74+p | | y=48x^2-3 | | 8n+6=19+7n | | -5(1-4a)=-5 | | -(3xy-11)+4(5xy+4)= | | 10b-4-6b=24-4 | | x^9-13x^8-14x^7=0 | | 8x-12=-4x+24 | | 2r^2+12rs-32s^2=0 |